Green Purchasing Decision: Peran Green Willingness to Purchase, Green Perceived Quality, dan Environmental Concerns - Sariyanti, Vita Kusumaningrum; Fikri, Muhammad Ali (https://jurnal.binamandiri.ac.id/, 2025)
Amid the growing public awareness of environmental issues, consumer behavior has shifted toward a preference for more eco-friendly products. This study aims to analyze the influence of green willingness to purchases and green perceived quality on green purchasing decisions, with environmental concern serving as a mediating variable. The research employs a quantitative approach by distributing questionnaires to N’Pure cosmetic consumers who are concerned about environmental issues. A total of 147 respondents participated in this study, and data analysis was conducted using SmartPLS 4.0. The results reveal that green willingness to purchase and green perceived quality have a positive effect on environmental concern. Furthermore, environmental concern positively influences green purchasing decisions. However, environmental concern does not mediate the relationship between green willingness to purchase and green purchasing decisions, while it does mediate the relationship between green perceived quality and green purchasing decisions. These findings highlight the importance of green perceived quality and consumer willingness to purchase as key drivers of green purchasing behavior, particularly when combined with a high level of environmental concern. The practical implications suggest that cosmetic producers such as N’Pure should continue to enhance the quality of their green products and strengthen environmental messaging within their marketing strategies to promote more sustainable purchasing decisions.